Why We Blog: Homeschooling Mothers of Gifted Children. Issue 2 (3rd April 2017) - Jolly, Jennifer L.; Matthews, Michael S.
Abstract : Blogs have become a go-to information resource for members of online communities. In this qualitative study we applied uses and gratifications theory (U&GT) to analyze the experiences and perceptions of four mothers of gifted children who maintain blogs about their homeschooling experiences. Data suggest that this novel context and population did not yield different categories of gratification; however, not all prior categories were represented among this relatively narrow sample. Results support findings from prior research in other contexts suggesting that bloggers find gratification from self-expression, social interaction, information exchange, maintaining community, and recording life events.